Mass Transfer and Fluid Hydrodynamics in Sealed End Hydrophobic Hollow Fiber Membrane Gas-liquid Contactors - Kartohardjono, S.; Chen, V. (Journal of Applied Membrane Science & Technology, 2017)
Hollow fiber membrane modules have been extensively used as gas-liquid contactor devices to provide a high surface area within a small volume. Hollow fiber membrane contactors have been demonstrated in a wide range of application such as in gas stripping and gas absorption. In this study the performance of sealed end hydrophobic microporous hollow fiber membranes contactors were evaluated to remove dissolved oxygen from water via vacuum degassing process. Hollow fibers membranes used in the experiment were hydrophobic microporous polypropylene of 650 Î¼m in outer diameter, 130 Î¼m wall thickness and nominal pore size of 0.2 Î¼m. Based on the experimental result the sealed end membrane contactor can remove oxygen from water as high as 3.4-gram oxygen per square meter of membrane area per hour. The oxygen flux decreases with increasing module-packing density for the same water velocity. The same effect also occurred for the mass transfer coefficient of the membrane contactors. The mass transfer coefficients were independent of fiber length within the range of study. Hydrodynamics analysis of the contactors showed that at the same Reynolds number pressure drops increase with increasing packing density due to an increase in friction between fibers and water.